2017
DOI: 10.1038/s41598-017-11576-4
|View full text |Cite
|
Sign up to set email alerts
|

Proxies of energy expenditure for marine mammals: an experimental test of “the time trap”

Abstract: Direct measures of energy expenditure are difficult to obtain in marine mammals, and accelerometry may be a useful proxy. Recently its utility has been questioned as some analyses derived their measure of activity level by calculating the sum of accelerometry-based values and then comparing this summation to summed (total) energy expenditure (the so-called “time trap”). To test this hypothesis, we measured oxygen consumption of captive fur seals and sea lions wearing accelerometers during submerged swimming an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Similarly, individual stroking costs in marine mammals and stride costs in terrestrial mammals can be used in combination with preferred stroke/stride rates as proxies for routine energy expenditure over short periods (Williams, Fuiman, et al, 2004; Williams, Kendall, et al, 2017; Williams, Blackwell, et al, 2017, but see Halsey, 2017; Ladds, Rosen, Slip, & Harcourt, 2017). Like terrestrial mammals for which the energetic cost per stride at routine speeds is nearly constant across body masses (mean = 7.0 J kg −1 stride −1 , SE = 0.6, n = 7; Heglund & Taylor, 1988), the energetic cost per stroke at preferred speeds generally appears to exhibit no significant trends across the body mass of marine mammals ( r 2 = 0.003, p = 0.85, n = 12, Figure 3c; table 3 in Williams et al., 2020).…”
Section: Landscape Energetics Of Large Predatory Mammalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, individual stroking costs in marine mammals and stride costs in terrestrial mammals can be used in combination with preferred stroke/stride rates as proxies for routine energy expenditure over short periods (Williams, Fuiman, et al, 2004; Williams, Kendall, et al, 2017; Williams, Blackwell, et al, 2017, but see Halsey, 2017; Ladds, Rosen, Slip, & Harcourt, 2017). Like terrestrial mammals for which the energetic cost per stride at routine speeds is nearly constant across body masses (mean = 7.0 J kg −1 stride −1 , SE = 0.6, n = 7; Heglund & Taylor, 1988), the energetic cost per stroke at preferred speeds generally appears to exhibit no significant trends across the body mass of marine mammals ( r 2 = 0.003, p = 0.85, n = 12, Figure 3c; table 3 in Williams et al., 2020).…”
Section: Landscape Energetics Of Large Predatory Mammalsmentioning
confidence: 99%
“…For example, a study evaluating the accuracy of stroke costs to measure energy expenditure of fur seals over a foraging trip that involved transit periods, diving and chasing and processing prey at sea found that this method poorly predicted total energy expended. In this case, the DBA method proved a better predictor of overall energy demand across long periods of interest (Halsey, 2017; Jeanniard‐du‐dot, Trites, Arnould, Speakman, & Guinet, 2016; Lads et al, 2017). Thus, when feasible, we recommend the use of DBA methods for measuring aerobic energy expenditure of carnivorous mammals, which appears to be a versatile metric for assessing both instantaneous and total energy expenditure, as well as for discriminating animal behaviours (Pagano & Williams, 2019).…”
Section: Landscape Energetics Of Large Predatory Mammalsmentioning
confidence: 99%
“…There have been a great number of studies in recent years that have attempted to link data from ETDs, such as accelerometry, activity partitioning, movement data or dive profiles, to robust models of energy usage over time. Using tag data that have not been properly calibrated to energy usage can be problematic and lead to spurious correlations and risks falling into the so-called 'time-trap' (merging measurements such that time is on both sides of an equation, as discussed in [40,66], but may be difficult to assess for certain species.…”
Section: Conclusion Caveats and Future Directionsmentioning
confidence: 99%
“…Dynamic body acceleration (DBA) or stroke rate, measured from accelerometers was promoted as a way to directly estimate energy expenditure in wild fur seals ( Jeanniard-du Dot et al, 2016 ). However, this approach has recently been shown to be flawed, as the apparent relationship between DBA and energy expenditure is in fact time correlated with time, as both the independent variable (energy) and dependent variable (DBA or strokes) are both summed, thus introducing time into both sides of the equation ( Halsey, 2017 ; Ladds et al, 2017a ). Thus, a new way of estimating energy expenditure is needed.…”
Section: Introductionmentioning
confidence: 99%